"Genetically Engineered" Biofunctional Triboelectric Nanogenerators Using Recombinant Spider Silk. Issue 50 (10th October 2018) - Zhang, Yujia; Zhou, Zhitao; Sun, Long; Liu, Zhen; Xia, Xiaoxia; Tao, Tiger H.
Abstract: Self‐powered electronics using triboelectric nanogenerators (TENGs) is drawing increasing efforts and rapid advancements in eco/biocompatible energy harvesting, intelligent sensing, and biomedical applications. Currently, the triboelectric performances are mainly determined by the pair materials' inherent electron affinity difference, and merely tuned by chemical or physical methods, which significantly limit the optional variety and output capability, especially for natural‐biomaterial‐based TENGs. Herein, a biocompatible triboelectric material with a programmable triboelectric property, multiple functionalization, large‐scale‐fabrication capability, and transcendent output performance is designed, by genetically engineering recombinant spider silk proteins (RSSP). Featuring totally "green" large‐scale manufacturing, the water lithography technique is introduced to the RSSP‐TENG with facilely adjustable surface morphology, chemically modifiable surface properties, and controllable protein conformation. By virtue of the high electrical power, a proof‐of‐principle drug‐free RSSP‐patch is built, showing outstanding antibacterial performances both in vitro and in vivo. This work provides a novel high‐performance biomaterial‐based TENG and extends its potential for multifunctional applications. Abstract : Recombinant spider silk proteins (RSSP) are genetically engineered, demonstrating a programmable triboelectric property, multiple functionalization, large‐scale‐fabrication capability, and transcendent output performance. Featuring totally "green" large‐scale manufacturing, the water lithography technique is conducted with facilely adjustable surface morphology, chemically modifiable surface properties, and controllable protein conformation. A proof‐of‐principle drug‐free RSSP‐patch is built, showing outstanding antibacterial performances both in vitro and in vivo.